2002
DOI: 10.1152/ajpheart.00946.2001
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic effects of cell volume on excitation-contraction coupling in rabbit ventricular myocytes

Abstract: .-We studied the effects of osmotic swelling on the components of excitation-contraction coupling in ventricular myocytes. Myocyte volume rapidly increased 30% in hyposmotic (0.6T) solution and was constant thereafter. Cell shortening transiently increased 31% after 4 min in 0.6T but then decreased to 68% of control after 20 min. In parallel, the L-type Ca 2ϩ current (ICa-L) transiently increased 10% and then declined to 70% of control. Similar biphasic effects on shortening were observed under current clamp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 42 publications
(79 reference statements)
4
30
0
4
Order By: Relevance
“…However, when the extracellular solution was further changed to 0.6 T, [Ca 2+ ] i was returned to the baseline (Figure 2Ba). Similarly, the increase of [Ca 2+ ] i induced by 1 T was absent in Ca 2+ free extracellular solution (Figure 2Bb), indicating that it might be attributed to enhanced Ca 2+ entry or reduced Ca 2+ extrusion by Na + -Ca 2+ exchanger [1,7,16] . All of these effects of osmotic stress on [Ca 2+ ] i were reversible.…”
Section: Effect Of Osmotic Stress On Spontaneous Camentioning
confidence: 89%
See 2 more Smart Citations
“…However, when the extracellular solution was further changed to 0.6 T, [Ca 2+ ] i was returned to the baseline (Figure 2Ba). Similarly, the increase of [Ca 2+ ] i induced by 1 T was absent in Ca 2+ free extracellular solution (Figure 2Bb), indicating that it might be attributed to enhanced Ca 2+ entry or reduced Ca 2+ extrusion by Na + -Ca 2+ exchanger [1,7,16] . All of these effects of osmotic stress on [Ca 2+ ] i were reversible.…”
Section: Effect Of Osmotic Stress On Spontaneous Camentioning
confidence: 89%
“…Furthermore, it has been shown that the increased blood tonicity in streptozotocin-induced diabetic rats leads to shrinkage of ventricular myocytes [5] . Many previous studies have indicated that both electrical and contractile properties of ventricular myocytes are affected by osmotic stress [1,[5][6][7][8][9] . For example, it has been consistently found that L-type Ca 2+ currents, Ca 2+ transients and contraction evoked by action potential are decreased by prolonged exposure to hyposmotic medium [1,7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brette et al had reported that in rat ventricular myocytes osmotic swelling decreases I Ca,L [16] . On the other hand, Li et al had found that in rabbit ventricular myocytes hyposmotic swelling induces biphasic changes, an increase followed by decrease, of I Ca,L under perforated whole-cell patch-clamp conditions [18] . In the present study, we found that osmotic swelling also induced biphasic changes of I Ca,L , a transient increase followed by sustained decrease, in rat ventricular myocytes (Figure 1).…”
Section: Discussionmentioning
confidence: 97%
“…For example, some studies have shown clear increases in I Ca,L [12][13][14] , while others have shown a decrease in I Ca,L [15,16] or no effect [10,17] . Some authors have even demonstrated biphasic effects on I Ca,L , an increase followed by a more sustained decrease [18] . Previous reports indicated that osmotic swelling increases I Ca,L in neonatal rat ventricular myocytes [14] , but decreases I Ca,L in adult rat ventricular myocytes [16] .…”
Section: Introductionmentioning
confidence: 99%